Individual low-energy E1 toroidal and compression states in light nuclei: Deformation effect, spectroscopy and interpretation - Nesterenko, Valentin; Kvasil, Jan; Repko, Anton; Reinhard, Paul-Gerhard (EPJ Web of Conferences, 2018)
The existence of individual low-energy E1 toroidal and compression states (TS and CS) in 24Mg was predicted recently in the framework of quasiparticle random phase approximation (QRPA) model with Skyrme forces. It was shown that the strong axial deformation of 24Mg is crucial to downshift the toroidal strength to the low-energy region and thus make the TS the lowest E1(K=1) dipole state. In this study, we explain this result by simple mean-field arguments. Comparing TS in two strongly axial nuclei, 24Mg and 20Ne, we show that the lowest TS is not a universal phenomenon but rather a peculiarity of 24Mg. The spectroscopy of TS and CS is analyzed and some additional interpretation of these states is suggested.
CRIS-Team Scopus Importer:2021-07-19